Medycyna: powołanie czy kalkulacja? Motywy wyboru studiów medycznych w świetle badań jakościowych - Makowska, Marta (Kultura-Społeczeństwo-Edukacja, 2025)
The aim of the article is to identify factors motivating young people to choose medical studies and to distinguish in their autonomous motivation and controlled motivation, as outlined by Self- Determination Theory (SDT). The study was conducted using focused group interviews with 92 students from three different medical universities in Poland. The participants had to be at least in their second year of studies. Thematic analysis was used to develop the results. All elements distinguished in SDT appeared in the study, i.e., concerning autonomous motivation: intrinsic motivation, with identified themes of the willingness to help, ambition, and pursuit of self-development. Identification and integration were also distinguished. Identification with the theme of the usefulness of studying, and integration with themes including: vocation, childhood, and personal choice. Regarding controlled motivation, a theme of prestige linked to introjection was identified, along with several themes related to external regulation, such as rewards, influence of significant others, familiarity with the profession. There were also statements about amotivation.